SAT0120 Characteristics Associated with Better Effectiveness and Safety in Rheumatoid Arthritis Patients Treated with Intravenous Tocilizumab: Results from Full Analysis of All-Patient Postmarketing Surveillance in Japan. (23rd January 2014) - Harigai, M.; Inokuma, S.; Ishiguro, N.; Ryu, J.; Takeuchi, T.; Takei, S.; Tanaka, Y.; Yamanaka, H.; Sano, Y.; Yaguramaki, H.; Koike, T.
Abstract : Objectives: This all-patient postmarketing surveillance aimed to evaluate the safety and effectiveness of tocilizumab (TCZ) for RA in the real-world clinical setting in Japan. Methods: Patients received 8 mg/kg TCZ every 4 weeks (wks) intravenously and were observed for 28 wks. Patient characteristics and safety and effectiveness data were collected. Multivariate logistic regression analysis was used to identify associated factors for outcomes and to calculate probability of achieving outcomes in each patient. To assess the benefit–risk balance of treatment, predicted probabilities (0–1) of developing serious infection were plotted against predicted probabilities (0–1) of achieving Boolean remission at wk 28. Results: A total of 7901 patients were enrolled. Incidence rates of total and serious adverse events (AEs) were 168.6/100 patient-year (pt-yr) and 27.4/100 pt-yr, respectively. The most common serious AEs were infections (9.0/100 pt-yr). Advanced age (≥65 years), long disease duration (≥10 years), previous or concurrent respiratory disease, and concomitant corticosteroid dose of >5 mg/day (prednisolone-equivalent) were risk factors for developing serious infections. The incidence rate of serious infections increased significantly in accordance with the number of baseline risk factors that each patient had (no risk factors, 1.18%; 1 risk factor, 2.98%; 2 risk factors, 5.24%; ≥3 risk factors, 11.15%, respectively at wk 28). The DAS28-ESR remission rate and Boolean remission rate were 47.6%, and 15.1%, respectively at wk 28. From the benefit–risk plot, we categorized 2 groups of patients: Group A, with a probability of remission >3 times the detected incidence (i.e. >45.3% at wk 28) and a probability of developing serious infection lower than the detected incidence (i.e. <3.8% at wk 28); and Group B, with a probability of remission equal to or less than the detected incidence (i.e. ≤15.1% at wk 28) and a probability of developing serious infection ≥2 times the detected incidence (i.e. ≥7.5% at wk 28). Group A showed shorter disease duration, less advanced RA, fewer comorbidities, less concomitant corticosteroid use, and less previous use of biologics (Table). Conclusions: This study demonstrates the safety and effectiveness of TCZ in patients with RA in the real-world clinical setting in Japan. Biologic-naïve patients with less advanced RA are the best candidates for treatment with TCZ. Disclosure of Interest: M. Harigai Grant/research support from: Abbott, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Santen, Takeda, UCB, and Pfizer, Consultant for: Abbott, Bristol-Myers Squibb, Chugai, and Janssen, Speakers bureau: Abbott, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Santen, Takeda, UCB, and Pfizer, S. Inokuma: None Declared, N. Ishiguro Consultant for: Abbott, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, Pfizer, and Takeda, Speakers bureau: Abbott, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, Pfizer, and Takeda, J. Ryu: None Declared, T. Takeuchi Grant/research support from: Abbott, Astellas, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, Janssen, Mitsubishi-Tanabe, Nippon Shinyaku, and Otsuka, Consultant for: Pfizer, Sanofi-Aventis, Santen, Takeda, Teijin, Astra Zeneca, Eli-Lilly, Novartis, Mitsubishi-Tanabe, and Asahi Kasei Medical, Speakers bureau: Abbott, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi-Tanabe, Pfizer, and Takeda, S. Takei Grant/research support from: Chugai, Eisai, Takeda, and Bristol-Myers, Speakers bureau: Chugai, Eisai, Takeda, Abbott, Astellas, Mitsubishi-Tanabe, and Asahi Kasei, Y. Tanaka Grant/research support from: Bristol-Myers Squibb, MSD, Chugai, Mitsubishi-Tanabe, Astellas, Abbott, Eisai, and Janssen, Consultant for: Mitsubishi-Tanabe, Abbott, Eisai, Chugai, Janssen, Santen, Pfizer, Astellas, Daiichi-Sankyo, GlaxoSmithKline, Astra-Zeneca, Otsuka, Actelion, Eli Lilly, Nippon Kayaku, UCB, Quintiles Transnational, Ono, and Novartis, Speakers bureau: Mitsubishi-Tanabe, Abbott, Eisai, Chugai, Janssen, Santen, Pfizer, Astellas, Daiichi-Sankyo, GlaxoSmithKline, Astra-Zeneca, Otsuka, Actelion, Eli Lilly, Nippon Kayaku, UCB, and Quintiles Transnational, H. Yamanaka Grant/research support from: Abbott, Bristol-Myers Squibb, Chugai, Eisai, Mitsubishi-Tanabe, Takeda, and Pfizer, Consultant for: Abbott, Bristol-Myers Squibb, Chugai, Eisai, Mitsubishi-Tanabe, Takeda, and Pfizer, Speakers bureau: Abbott, Chugai, Eisai, Mitsubishi-Tanabe, Takeda, and Pfizer, Y. Sano Employee of: Chugai, H. Yaguramaki Employee of: Chugai, T. Koike Speakers bureau: Chugai, Mitsubishi-Tanabe, Pfizer, Astelas, BMS, UCB, Takeda, Taisyo-Toyama, Eisai, Abbott, Teijin, and Santen